A case of penile basal cell carcinoma reconstructed by scrotal myofasciocutaneous flap. Issue 5 (6th June 2016) - Hoashi, Toshihiko; Kikuchi, Kanako; Sato, Shinichi; Saeki, Hidehisa
Abstract: Basal cell carcinoma is the most common cutaneous malignant tumor and usually arises from the facial skin and is diagnosed as the solid tumor. However, rarely it arises from genital skin and/or proceeds with ulcerative manner. We report a case of male basal cell carcinoma arising from penile base, which showed urinary disturbance. Tumor resection including total penectomy and skin resection was performed then scrotal myofasciocutaneous flap was used to cover the defect. Scrotal myofasciocutaneous flap was useful for covering the defect in the genital lesion. Moreover, this simple closure was helpful for early postoperative ambulation especially for aged male patients.